Analysis of the Mechanical Properties of SMAW Welded Joints on ST 37 Plate Material after PWHT as a Case Study in Welding Engineering Education - Qulfaj, Asadda; A, Aljufri; Rizki, Muhammad Nuzan; Islami, Nurul; Isra, Muhammad (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
One of the techniques in improving the mechanical properties of a welding result is the Post Weld Heat Treatment (PWHT) process. Attempts to improve these properties are the main goal of users so that the construction they build can last a long time from the influence of natural phenomena. This research aims to analyze the mechanical properties of SMAW welded joints on ST37 plate material that undergoes the PWHT process, as well as contribute as a practicum teaching material or case study in learning welding techniques in the technical education environment. In this study, welding was carried out with E7016 electrodes, and then three variations of the PWHT process were carried out, namely at temperatures of 400, 500, and 600°C with a holding time of 30, 60, and 90 minutes, respectively. The joints were tested using a penetrant test and a hardness test. The results showed that PWHT at 600°C with a holding time of 90 minutes produced the highest average hardness value compared to 400°C and 500°C with 30 and 60 minutes. This finding reinforces the understanding that temperature and holding time in the PWHT process significantly affect the hardness value of the weld. Therefore, the results of this study are not only useful in the development of manufacturing technology but also utilized as an applicable learning medium. By knowing the effect of PWHT on the mechanical properties of welded joints, welding instructors can design a more effective practicum in teaching the principles of welding.